Exploring the meaning of cardiovascular disease with Māori men : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Health Psychology at Massey University, Albany, New Zealand - Lisipeki, Samantha (Massey University, 2019)
Ethnic disparities in health outcomes are an ongoing concern in Aotearoa/New Zealand. These disparities are particularly pronounced between Māori and non-Māori, and are especially apparent for cardiovascular disease (CVD). Despite these well-known disparities, research into how the social determinants of health manifest in the context of Māori people’s everyday lives and experiences of CVD is limited. Using a narrative approach, this research documents Māori male patients’ experiences of CVD within the context of everyday life. Four Māori males who have experienced cardiovascular care were recruited through the Waikato District Health Board secondary prevention service. The patients and their whānau (family) who wished to participate were engaged in three separate semi-structured interviews which explored topics involving their CVD diagnosis, experiences of CVD, their steps to accessing care and experiences of care. Overall, the cases revealed three key findings. First, various factors work in concert to influence participant access to cardiac care, which extend beyond individual decision making (such as structures of everyday life and resources). Second, there is considerable diversity in participant life circumstances, which are related to their experiences of care and its outcomes. Third, CVD impacted the lives of my participants differently and contributed to varying levels of illness disruption to their life narratives. This study contributes to a growing body of knowledge for addressing disparities in health outcomes between Māori and non-Māori.
Keywords: Cardiovascular system; Diseases; Patients; New Zealand; Maori (New Zealand people); Medical care; Men; Health and hygiene; Attitudes; Tāne; Tāngata whenua; Tūroro; Pūnaha toto; Hauora